Efficacy of the treatment for elderly emergency patients with sepsis. Issue 5 (May 2021) - Isshiki, Yuta; Nakajima, Jun; Sawada, Yusuke; Ichikawa, Yumi; Fukushima, Kazunori; Aramaki, Yuto; Oshima, Kiyohiro
Abstract: Objectives: We evaluated the impact of age in septic patients admitted through the ER on clinical outcome and cost. Methods: Patients with sepsis admitted to the intensive care unit (ICU) through the emergency room in our hospital between January 2013 and December 2018 were analyzed. They were divided into three groups according to their age: <65 years (group Y); 65–79 years (group M); and ≥80 years (group E). The duration of ICU and hospital stay, prognosis, and total hospital costs were compared among the three groups. Results: During this period, 1, 392 patients were admitted to the ICU through the emergency room, and 174 patients with sepsis were analyzed. There were 49, 79, and 46 patients in groups Y, M, and E, respectively. There was no significant difference in ICU stay. Group E exhibited the shortest hospital stay and the lowest total hospital cost with statistically significant difference (p = 0.010 and p = 0.007, respectively). However, group E showed the highest rate of hospital mortality (30.4%) compared to groups Y and M (14.3% and 21.5%, respectively; p = 0.163). Conclusions: Elderly (aged ≥80 years) emergency patients with sepsis require shorter hospital stay and are associated with lower total hospital cost. However, it may be difficult for these patients to maintain the hospital mortality equivalent to those observed in patients aged <80 years. Abstract : Sepsis, Intensive care, Elderly.